The role of ADR and judicial agreements: legal analysis and behavioral economics insights - Solano Mantilla, Valeria (LUISS Guido Carli, 2025)
From rationality to reality. The evolution of law and economics through the behavioral lens. Understanding how we choose: foundations of behavioral economics. Rethinking law through the lens of behavioral economics. Why law needs behavioral economics. The challenge of integrating behavioral economics into private law: freedom vs regulation. The double-edged sword of behavioral economics: protecting consumers from psychological manipulation. Balancing innovation and consumer rights: a global view on consumer protection in the EU, Italy and Colombia. Alternative dispute resolution and the judicial agreements. The justice system seen though behavioral economics. Judicial agreements: procedural autonomy and enhancing judicial cooperation. Alternative dispute resolution (ADR) and mediation: legal frameworks, party autonomy and behavioral economic. A brief comparative analysis on mediation: EU, Italy and Colombia. Applying behavioral economics in the ADR (mediation).
Keywords: ADR; Alternative dispute resolution; Economic behaviour; Mediation; Médiation

The efficacy of commercial arbitration, law and practice Lesotho - Thethe-Chitja, Makabelo (National University of Lesotho, 2023)
The success of commercial arbitration law and practice is achieved as a result of several factors. The purpose of the study was to investigate whether efficacy of commercial arbitration, law and practice in Lesotho is hindered by the legal framework which does not conform to the United Nations Commission Trade Law on International Commercial Arbitration, UNCITRAL Model Law. Examining such other factors as support of the courts and government, the study specifically investigated the impact of lack of education about commercial arbitration for the business community and unregulated arbitrators on the efficacy of the commercial arbitration, law and practice in Lesotho. With the use of the desk reviews and interviews as data collection methods for this study, the evidence obtained has revealed that efficacy of the commercial arbitration, law and practice in Lesotho is hampered by the law which is outdated and inconsistent with the UNCITRAL Model law. As such, support for the mechanism by the courts has been found to be at stake or adversely affected. Lack of support from the government and that of awareness campaigns about the mechanism for the business community have also been noted for constraining the efficacy of the commercial arbitration, law and practice in the country. Further noticeable from the findings include limited commitment from the legal profession and unregulated arbitrators, both of which could have significantly obstructed the mechanism. The study thus concludes that there is an urgent need for law reforms and concerted commitment from the relevant stakeholders to help towards achieving efficacy of the commercial arbitration, law and practice in Lesotho.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration; Lesotho

Dissenting Opinions in International Commercial Arbitrations - Mohanty, Gautam (Central European University, 2017)
A dissenting opinion with reference to International Commercial Arbitrations elementarily denotes the expression of disagreement by an Arbitrator in relation to both the reasoning and the result of the award granted by the majority of the Tribunal. Though still at a nascent stage, the practice of delivering dissenting opinions is one which needs to be duly noted and taken into due consideration because of the incidental and collateral questions that it nurtures. Fundamentally, a dissenting opinion raises concerns related to the effect, the nature and the rectitude of such opinions. One such collateral question is the enforceability of such dissenting opinions and the repercussions that follow in the context of an arbitral award delivered by the majority. In addition to the above raised question, through this thesis the author will also address other questions such as whether the act of delivering a dissenting opinion is an indicator of the increased sense of maturity of arbitrators in international commercial arbitration? Whether the dissenting opinion possesses any precedential value to the arbitration cases arriving prospectively? and How do such opinions contribute to the development of arbitration jurisprudence. Moreover, through this thesis the author will also attempt from a comparative perspective to examine and make an incisive analysis of the governing rules of arbitration across various arbitration regimes such as ICSID, LCIA which already have a wellestablished arbitration jurisprudence.

Alternative Dispute Resolution in Oil and Gas Contracts Law: An Analysis - Kareem, Kareem Kawa (Near East University, 2017)
The industry of oil and gas is not peculiar to question anymore, inferable from the global condition as well as its various dimensions. While trying to complete an agreement procedure, it would barely be clear to expect the thing that could happen in the emergence of a debate. Hazard moving and fragmented contracting lie at the heart of the organization relationship innate in the obtainment and financing of extensive scale undertakings, such as power plants, oil and gas pipelines, and condensed natural gas facilities. An examination of gas bonds gives exact proof of the hazard moving results of legally binding inadequacy. This thesis is a basic examination of the discipline we call the law of oil and gas. A number of the imperfections connected with this "specific" status. Jurisprudential with its "uncommon" status. Jurisprudential imperfections have created as courts leave from essential contract, property, or tort law in quest for natural resources ideas. The marvel isn’t restricted to natural resources law but instead can occur in any "law of" setting. This article delineates the issues connected with oil and gas law by dissecting legal ways to deal with perceiving and applying "inferred agreements" under the oil and gas rent. By contrasting the experience and results under the oil and gas lead to the result under an agreement law investigation, it is conceivable to assess whether a specific "oil and gas" govern is vital or prudent. In the past quarter-century, huge changes have happened in the ways legal advisors approach strife. There have been uncommon endeavors to create systems went for more proficient, not so much expensive, but rather more fulfilling determination of contention, including more broad and suitable utilization of intercession and other " alternative dispute resolution " (ADR) approaches. This review analyzes what is known and not considered about the development and effect of ADR in government and state courts, in the business division, and in work and shopper settings. The investigation inspects the relationship amongst ADR and court trial, additionally underlines the more extensive employments of and method of reasoning for intercession and different process decisions. This study concentrates on the oil and gas contract with question by ADR.

State interference through domestic courts in international commercial arbitration - Badenhorst, Casper Hendrik Jacobus (University of Johannesburg, 2016)
Keywords: Arbitrage; Arbitragem; Arbitration; International and municipal law; International commercial arbitration

Mediation advocacy - Shaw, Annabel (Victoria University of Wellington, 2014)
Mediation has been a part of New Zealand’s employment statutory framework in one form or another for over a century, and has been the first port of call for employment disputes under the current Employment Relations Act for nearly 15 years.¹ I have been working as a mediator in this context for almost seven years in more than 1,000 mediations. Lawyers are playing a significant part in the field of mediation, with a large number representing clients in this forum on a regular basis. In an evaluation of 100 of my mediations over a ten-month period, 85% of parties were legally represented. This rate is consistent with anecdotal reporting across the employment mediation service. Lawyer representation in mediation is not unique to the employment context. There are various mediation schemes provided for under many New Zealand statutes as well as a wide raft of non-statutory mediation occurring in numerous settings. In my experience as a mediator with human rights and leaky building mediations, as well as working as a lawyer in a large commercial law firm, I am aware lawyers are representing clients in many other areas of mediation as well. Although there is a significant amount of mediation occurring and a large number of lawyers regularly appearing in mediation, my experience is that the majority of lawyers act in mediation as if they were in litigation and take an adversarial approach. My thesis is that lawyers have not adapted effectively to mediation and taken on the role of mediation advocacy. This paper explores the topic by first describing, in Part II, what I observe as lawyers’ adversarial approach in mediation. It then looks at other research to assess whether this experience is reflective of a wider issue. It finds there is evidence to support my observations. Part III analyses why lawyers are operating in an adversarial way in mediation and proposes several reasons this may be the case. Part IV puts forward what I propose is appropriate mediation advocacy. It sets out the knowledge, roles and skills required from lawyers when representing clients in mediation. Part V suggests what might be done to assist a shift away from the common, adversarial approach to effective mediation advocacy. This paper is written within the context of employment mediation in New Zealand. However, it draws on research from different jurisdictions and areas of practice so the conclusions it comes to may have more general application. The topic is not whether lawyers should be in mediation. I am not arguing that lawyers do not have a part to play in mediation. A lawyer well versed in mediation advocacy can play a highly effective part in the process. Leonard Riskin, one of the key authors on the topic of lawyers in mediation, expresses this even more strongly, saying he believes lawyers’ involvement is fundamental to mediation’s success.² Further, this paper is focused on lawyers representing parties in mediation and does not consider lawyers as mediators.
Keywords: Advocacy; Dispute resolution; Employment disputes; Lawyers; Mediation

The Influence of ICC Arbitral Decisions on Canadian Law: Comparative Study between Civil Law and Common Law Jurisdictions - Hedaraly, Saleha (Université de Montréal, 2012)
L’objectif de cette recherche est de démontrer que les décisions arbitrales de la Chambre de commerce internationale peuvent être considérées comme une source potentielle de droit au Canada. Il existe actuellement une incertitude quant au droit matériel utilisé en arbitrage international pour résoudre les différends commerciaux. Bien que l’utilisation de la lex mercatoria pour résoudre un litige soit une option, elle se heurte à de nombreuses incertitudes terminologiques et conceptuelles. L’utilisation d’une approche méthodologique de la lex mercatoria permettrait une classification de ses sources en deux branches: (1) le droit statutaire international et (2) le stare decisis des tribunaux d’arbitrage commercial international. Une telle approche méthodologique conférerait plus de certitude quant à l’application d’un droit uniforme. De plus, elle faciliterait l’étude de l’interlégalité entre les règles de la lex mercatoria et le droit matériel interne. Plus particulièrement, elle permet de comparer les similitudes et les différences des règles du droit matériel entre les décisions arbitrales internationales, le droit statutaire international et les juridictions canadiennes de common law et de droit civil. Cette comparaison rend possible une évaluation de l’influence potentielle des décisions arbitrales de la Chambre de commerce internationale sur le droit matériel canadien et si cette influence est plus importante en droit civil ou en common law. This paper’s objective is to demonstrate that the International Chamber of Commerce’s arbitral awards may be considered as a potential source of law in Canada. There currently exists an uncertainty as to the substantive law used in international commercial arbitration. While the use of lex mercatoria to solve commercial disputes is often referred to, several terminological and conceptual uncertainties undermine its credibility. The use of a methodological approach to lex mercatoria allows for a twofold classification of its sources through: (1) international legislation and (2) stare decisis from international arbitral tribunals. This methodological approach provides a greater certainty for the application of a uniform law which, in turn, allows for the study of interlegality between rules of lex mercatoria and substantive domestic law. Furthermore, this methodological approach facilitates the demonstration of the similarities and differences between international arbitral decisions, international legislation as well as Canadian common law and civil law jurisdictions. This comparative analysis will allow the study of the potential influence of the arbitral decisions of the International Chamber of Commerce on substantive Canadian law and whether this influence is more important in civil law or common law.
https://papyrus.bib.umontreal.ca/xmlui/bitstream/handle/1866/12719/Hedaraly_Saleha_2012_memoire.pdf
Keywords: Approche méthodologique; Arbitrage; Arbitragem; Arbitral decisions; Arbitration; CCI; Civil law; Common law; Droit civil; Droit commercial transnational; Décisions arbitrales; ICC; Interlegality; Interlégalité; Lex mercatoria; Methodological approach; Sentences arbitrales; Transnational commercial law